Fulfilling the Pakistan Vision of Quaid-i-Azam (The Quaid-i-Azam Lecture) (The Pakistan Development Review, 2015)
In this lecture I will begin by suggesting that economic equality is one of the founding principles of Pakistan in terms of the explicitly stated view of Quaid-i-Azam Muhammad Ali Jinnah and also in the Constitution of Pakistan. I will in section-II indicate the analytical basis of growth policies followed by Pakistan’s policy-makers in the decades after independence and the consequent inequality and mass poverty that persist till today. In the next Section-III, I will discuss recent research to lay the basis of an alternative perspective on economic growth which can provide the framework for fulfilling the Pakistan vision. In the final Section-IV, I will outline three main features of a new inclusive development strategy. It will be argued that if a prosperous future for Pakistan is to be achieved then a change in the institutional structure is required whereby all of the people rather than only a few have opportunities to fulfill their human potential. Thus Pakistan can be placed on a new trajectory of sustained and equitable growth.